A Preliminary Study on Human Placental Tissue Impaired by Gestational Diabetes: A Comparison of Gel-Based versus Gel-Free Proteomics Approaches. Issue 2 (April 2016) - Roverso, Marco; Brioschi, Maura; Banfi, Cristina; Visentin, Silvia; Burlina, Silvia; Seraglia, Roberta; Traldi, Pietro; Lapolla, Annunziata
Gestational diabetes (GDM) is the most common complication of pregnancy and it is associated with maternal and fetal short- and long-term consequences. GDM modifies placental structure and function, but many of the underlying mechanisms are still unclear. The aim of this study is to develop and compare two different methods, based respectively on gel-based and gel-free proteomics, in order to investigate the placental proteome in the absence or in the presence of GDM and to identify, through a comparative approach, possible changes in protein expression due to the GDM condition. Placenta homogenates obtained by pooling six control samples and six samples from GDM pregnant women were analyzed by two-dimensional (2D) electrophoresis coupled with mass spectrometry [nano-liquid chromatography (nano-LC) tandem mass spectrometry (MS/MS) and matrix-assisted laser desorption/ionization mass spectrometry (MALDI-MS)] and by a label-free mass spectrometry method based on LC-MS E . The gel-based approach highlights 13 over-expressed proteins and 16 under-expressed proteins, while the label-free method shows the over-expression of 10 proteins and the under-expression of nine proteins. As regards 2D gel electrophoresis, a comparison between two different protein identification methods, based respectively on nLC-electrospray ionization-MS/MS and MALDI-MS/MS, was performed taking into consideration the sequence coverage, the MASCOT score and the exponentially modified protein abundance index. The analysis of the complex proteome through an integrated strategy revealed that the quantitative gel-free and label-free MS approach might be suitable to identify candidate markers of GDM.